2013 IEEE Student Conference on Research and Developement 2013
DOI: 10.1109/scored.2013.7002548
|View full text |Cite
|
Sign up to set email alerts
|

Battery energy storage system for PV output leveling based on bidirectional isolated DC-DC converter

Abstract: A photovoltaic (PV) system has a variable power output that depends on solar irradiance level and ambient temperature. This will be an issue when there is a massive penetration of PV in the future. Therefore, an energy storage system is indispensable to compensate the problem of PV output fluctuations. Battery energy storage system (BESS) employing power electronic converters can be used for compensating the fluctuating PV power. This paper proposes a 2-kW full-bridge bidirectional isolated dc-dc converter tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The latter solution seems not to be of common usage. Indeed, most of the research works in the literature analyse the other two solutions, as reported in [3–7]. Instead, in [8], the authors use the last solution where the charge and discharge of the battery is demanded to the dc–ac converter.…”
Section: Introductionmentioning
confidence: 99%
“…The latter solution seems not to be of common usage. Indeed, most of the research works in the literature analyse the other two solutions, as reported in [3–7]. Instead, in [8], the authors use the last solution where the charge and discharge of the battery is demanded to the dc–ac converter.…”
Section: Introductionmentioning
confidence: 99%
“…There are various power converters for the storage system with a different number of switches [87]. Among all the power converters, the synchronous boost DC-DC converter [88,89] and the dual active bridge converter [90][91][92][93] Output Capacitor 820 C The distribution generation system in a DC distribution system is usually renewable energy such as photovoltaic and wind energy. For a country in the topical zone such as Singapore has rich sunlight and the photovoltaic is the most common distributed generation source in the DC distribution system.…”
Section: Microgrid System Configurationmentioning
confidence: 99%